The Effect of 10 weeks of high-intensity exercise training on resting levels of some angiogenesis and pulmonary function of men with prostate cancer - FGHJK DFGHJK; DFGHJK DFGHJ; DFGHJK DFGHJK (Fasa University of Medical Sciences, 2018)
Background & Objective: Prostate cancer is the most common malignancy and the eighth cause of death in Iran. Angiogenesis is the major cause of metastatic and drug resistance in this cancer. The aim of this study was to investigate the effects of 10 weeks of high intensity periodic exercises on resting levels of some angiogenesis markers and also the pulmonary function of men with prostate cancer. Materials & Methoed: 20 male patients with prostate cancer aged 55 to 62 years old were randomly divided into two groups (n = 10) and experimental (n = 10). The experimental group subjected to 10 weeks of periodic exercise with intensity progressed weekly, three sessions for 40 minutes and intensity of 70-75 was set for each session. 48 hours before and after exercise, the serum levels of VEGF, FGF, nitric oxide (NO) and also pulmonary function were measured. Intra and intergroup changes were analyzed using dependent t-test and independent t-test, respectively. Results: The results showed that 10 weeks of severe periodic training significantly increased the levels of VEGF (P = 0.001), FGF (P = 0.001) and NO (P = 0.001) in the experimental group compared with the control group. Moreover, considering the results, FVC in patients with periodic exercise has increased significantly (P = 0.002). Conclusion: As for results, it can be concluded that 10 weeks of periodic exercise increases the angiogenesis and pulmonary function in patients suffered from prostate cancer.